Salmonella enterica serovar Typhi influences inflammation and autophagy in macrophages - Wang, Huiyun; Xie, Zhongyi; Yang, Fanfan; Wang, Yurou; Jiang, Haiqiang; Huang, Xinxiang; Zhang, Ying (Brazilian journal of microbiology, 2022)
Salmonella enterica serovar Typhi ( S. Typhi) is a human enteropathogen that can survive in macrophages and cause systemic infection. Autophagy and inflammation are two important immune responses of macrophages that contribute to the elimination of pathogens. However, Salmonella has derived many strategies to evade inflammation and autophagy. This study investigated inflammation-related NF-κB signaling pathways and autophagy in S. Typhi-infected macrophages. RNA-seq and quantitative real-time PCR indicated that mRNA levels of NF-κB signaling pathway and autophagy-related genes were dynamically influenced in S. Typhi-infected macrophages. Western blots revealed that S. Typhi activated the NF-κB signaling pathway and induced the expression of inhibitor protein IκBζ. In addition, S . Typhi enhanced autophagy during early stages of infection and may inhibit autophagy during late stages of infection. Thus, we propose that S. Typhi can influence the NF-κB signaling pathway and autophagy in macrophages.